Solve for j 4j-(2j-3)=8-3j

Math
4j-(2j-3)=8-3j
Simplify 4j-(2j-3).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
4j-(2j)–3=8-3j
Multiply 2 by -1.
4j-2j–3=8-3j
Multiply -1 by -3.
4j-2j+3=8-3j
4j-2j+3=8-3j
Subtract 2j from 4j.
2j+3=8-3j
2j+3=8-3j
Move all terms containing j to the left side of the equation.
Tap for more steps…
Add 3j to both sides of the equation.
2j+3+3j=8
Add 2j and 3j.
5j+3=8
5j+3=8
Move all terms not containing j to the right side of the equation.
Tap for more steps…
Subtract 3 from both sides of the equation.
5j=8-3
Subtract 3 from 8.
5j=5
5j=5
Divide each term by 5 and simplify.
Tap for more steps…
Divide each term in 5j=5 by 5.
5j5=55
Cancel the common factor of 5.
Tap for more steps…
Cancel the common factor.
5j5=55
Divide j by 1.
j=55
j=55
Divide 5 by 5.
j=1
j=1
Solve for j 4j-(2j-3)=8-3j

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top